Histones H1 and H5 interact preferentially with crossovers of double-helical DNA. - Krylov, D (1993)
The interaction of the linker histones H1 and H5 from chicken erythrocyte chromatin with pBR322 was studied as a function of the number of superhelical turns in circular plasmid molecules. Supercoiled plasmid DNA was relaxed with topoisomerase I so that a population with a narrow distribution of topoisomers, containing from zero to five superhelical turns, was obtained. None of the topoisomers contained alternative non-B-DNA structures. Histone-DNA complexes formed at either 25 or 100 mM NaCl final concentration and at histone-DNA molar ratios ranging from 10 to 150 were analyzed by agarose gel electrophoresis. The patterns of disappearance of individual topoisomer bands from the gel were interpreted as an indication of preference of the linker histones for crossovers of double-helical DNA. This preference was observed at both salt concentrations, being more pronounced under conditions of low ionic strength. Isolated H5 globular domain also caused selective disappearance of topoisomers from the gel, but it did so only at very high peptide-DNA molar ratios. The observed preference of the linker histones for crossovers of double-helical DNA is viewed as a part of the mechanism involved in the sealing of the two turns of DNA around the histone octamer.